A 1642 Ma age for the Fraynes Formation, Birrindudu Basin, confirms correlation with the economically significant Barney Creek Formation, McArthur Basin, Northern Territory. Issue 3 (2nd April 2020) - Munson, T. J.; Denyszyn, S. W.; Simmons, J. M.; Kunzmann, M.
Abstract: An interpreted CA–IDTIMS age of 1642.2 ± 3.9 Ma for a volcanogenic tuffaceous siltstone from the previously undated Fraynes Formation of the Birrindudu Basin in the northwestern Northern Territory enables a rigorous chronostratigraphic correlation to be made with the economically important Barney Creek Formation of the southern McArthur Basin. This result supports previous interpretations that these geographically widely separated formations are probably linked in the subsurface. It also establishes the stratigraphic interval encompassing the Fraynes and Barney Creek formations as a potential target for greenfields base metals and petroleum exploration programs across the greater McArthur Basin. KEY POINTS: A new interpreted CA–IDTIMS age provides a chronostratigraphic link between the Fraynes Formation of the Birrindudu Basin and the economically important Barney Creek Formation of the southern McArthur Basin. The Fraynes and Barney Creek formations are probably linked in the subsurface. This stratigraphic level is a potential target for greenfields base metals and petroleum exploration across the greater McArthur Basin.